A molecular sieve composite catalyst and a method for producing light olefins and aromatics from naphtha by oxidation and cracking

By using molecular sieve composite catalyst, combined with Pechini sol-gel method and ion exchange method, the modified perovskite-molecular sieve composite catalyst was solved, and the problems of high energy consumption, low olefin yield and easy catalyst carbon deactivation in naphtha cracking technology were solved, achieving high efficiency and low energy consumption of low-carbon olefin preparation.

CN119215972BActive Publication Date: 2025-03-04XIANGTAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411717926.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing low-carbon olefin technology for naphtha cracking has problems such as high energy consumption, high device cost, low olefin yield, unstable product distribution and easy catalyst carbon deactivation.

Method used

A molecular sieve composite catalyst was used to prepare alkali metal salt-modified ABO3 perovskite composite oxygen carrier by using the Pechini sol-gel method and impregnation method, and a metal-modified molecular sieve was prepared by ion exchange method to form a modified perovskite-molecular sieve composite catalyst, which was used for naphtha oxidation and cracking reaction.

Benefits of technology

It improves the yield of low-carbon olefins and aromatics, reduces reaction temperature, enhances the catalyst's coke resistance, reduces energy consumption, and avoids safety hazards and COX excessive emission problems in traditional oxidation and cracking technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present invention provides a molecular sieve composite catalyst, the composition of the catalyst is: T-ZSM-5(r) & L-Na2MoO4@CaMn 0.8 F 0.2 O3, wherein T = Ca, Mg, Y, Zr, Sr, r = 50, 80, 130, 200, 260, F = Cu, Fe, Co, Mo, L = 0, 10%, 20%, 30%, 40%. The present invention also provides a novel method for preparing low-carbon olefins and aromatics by oxidative cracking of naphtha, wherein the composite catalyst is loaded into a fixed bed reactor, and naphtha and nitrogen are introduced into the reactor to control the reaction under certain conditions. The technology of preparing low-carbon olefins by oxidative cracking of naphtha based on chemical chain technology of the present invention realizes the efficient conversion of naphtha into low-carbon olefins, effectively reduces the reaction energy consumption and CO X It reduces emissions and effectively avoids the problem of traditional molecular sieve catalysts being prone to carbon deposition and deactivation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparing light olefins and aromatics through cracking of naphtha, and in particular to a molecular sieve composite catalyst and a novel method for preparing light olefins and aromatics through oxidative cracking of naphtha. Background Art

[0002] As the cornerstone of the modern chemical industry, low-carbon olefins (C2 = ~ C4 = ) is an important basic chemical raw material in the petrochemical industry and is widely used in rubber, polymers, pesticides, medicines, fine chemicals and other fields.

[0003] As the demand for low-carbon olefins increases, its production process technology has also shown diversified development. The main production methods include oil production (mainly naphtha cracking), coal production (including purchased methanol) and light hydrocarbon cracking. So far, the industrial production of low-carbon olefins is still dominated by naphtha cracking technology, but it is also facing the pressure of eliminating backward production capacity and insufficient supply of light raw materials.

[0004] Currently, the technologies for producing low-carbon olefins by cracking naphtha mainly include: steam thermal cracking and catalytic cracking.

[0005] 1. Naphtha steam thermal cracking technology

[0006] Steam cracking technology is to crack petroleum hydrocarbons under high temperature and water vapor conditions to decompose saturated hydrocarbons into smaller unsaturated hydrocarbons. Most steam cracking technologies use tubular cracking furnaces. There is no catalyst involved in the reaction process. There are more C1 and C2 substances in the products, and ethylene and propylene are produced as by-products. Steam cracking technology has a long history of development and mature technology. It occupies an important position in the global chemical raw materials market and is currently the most important process for producing ethylene and propylene. Its low-carbon olefin production capacity accounts for more than 90% of the total ethylene production and more than 50% of the total propylene production.

[0007] 2. Naphtha catalytic cracking technology

[0008] Compared with steam cracking technology, catalytic cracking technology is to introduce catalysts into the reaction system to reduce the activation energy of the CC bond and CH bond breakage of hydrocarbon substances in the reaction, and then the cracking reaction process produces olefins and CO X, and aromatic hydrocarbons. The process has a wide adaptability to raw materials (can be divided into crude oil, distillate oil or heavy oil), effectively reduces the reaction temperature (600~750 ℃), has a high yield of light olefins, and has good product adjustability. It is especially suitable for light conversion of heavy oil. Among them, the catalyst is the core of the catalytic cracking process, which requires it to have good and appropriate acidity, selectivity, hydrothermal stability and anti-coking ability. At present, the catalysts used in catalytic cracking technology are mainly molecular sieve catalysts and metal oxide catalysts. The existing processes can be divided into oxygen-free catalytic cracking and oxidative cracking with oxygen according to the participation of oxygen or not.

[0009] 2.1 Anaerobic catalytic cracking technology

[0010] Currently, representative catalytic cracking technologies at home and abroad include: the DCC process and CPP process developed by Sinopec Petrochemical Research Institute (ethylene, propylene and butene account for 20.37%, 18.32% and 7.52% respectively), the HCC process technology developed by Sinopec Luoyang Petrochemical (ethylene yield 25~27%), the TMP process technology developed by China University of Petroleum, the TCSC cracking process developed by the German Center for Organic Chemistry Research, the Superflex process technology developed by Mobil, the JPCA process developed by the Japan Petrochemical Industry Association and the THR process technology developed by Toyo Corporation of Japan.

[0011] 2.2 Oxidative cracking technology with oxygen

[0012] Oxidative cracking technology with oxygen co-feed is to introduce petroleum hydrocarbon raw materials and oxygen into the reaction device in a certain ratio, and crack them under the action of molecular sieve or transition metal oxide catalyst. Compared with oxygen-free catalytic cracking, the advantages of catalytic cracking technology with oxygen co-feed are: (I) It breaks the thermodynamic equilibrium under catalytic cracking of crude oil. The large amount of hydrogen produced as a by-product in the catalytic cracking reaction causes the reaction equilibrium to shift to the left. The addition of oxygen causes part of the hydrogen to be burned, thereby increasing the conversion of substrate hydrocarbons; (II) The oxygen atmosphere promotes the conversion of coke into CO X (CO, CO2), which can effectively avoid carbon deposition and deactivation of the catalyst; (III). The addition of oxygen transforms the cracking process from an endothermic process to an exothermic process, further reducing the reaction temperature and the required energy supply cost.

[0013] The main technical problems of existing methods are as follows:

[0014] 1. Steam thermal cracking technology

[0015] In the steam cracking process based on the free radical mechanism, the product distribution is restricted by many factors, such as the composition of the raw materials, the cracking temperature, the residence time in the cracking furnace, and the ratio of hydrocarbon substances to steam. Among them, the properties of the raw materials have a decisive influence on the cracking results. As a cracking raw material, the content of alkanes and cycloalkanes in the composition of naphtha is required to be not less than 70% (volume).

[0016] The main disadvantages of steam pyrolysis technology:

[0017] 1) The reaction process consumes a lot of energy, accounting for about 40% of the total energy consumption of the entire petrochemical process;

[0018] 2) High equipment cost. Due to its strong heat absorption characteristics, the cracking furnace needs to withstand high temperatures exceeding 1000°C, requiring expensive high-temperature resistant materials and equipment; in addition, high temperatures will also affect the service life of the equipment;

[0019] 3) The olefin yield is low and the ratio control is limited. The process also produces a large amount of NO. X and CO X And other harmful gases;

[0020] 4) Poor production continuity. Regular treatment of coking seriously affects production continuity, and the optimized steam cracking process can only alleviate the coking problem but cannot eliminate it.

[0021] 2. Catalytic cracking technology

[0022] The catalytic cracking process is jointly regulated by the carbon cation mechanism and the free radical reaction mechanism. In the low-temperature cracking process using acidic molecular sieves as catalysts, the carbon cation mechanism is dominant; in the high-temperature cracking process using metal oxide catalysts, the free radical mechanism is dominant; therefore, the catalytic cracking reaction process is not easy to control. In addition, the rationality of the existing catalytic cracking reaction mechanism is general, and there is an urgent need to propose a universal reaction mechanism to guide the development and improvement of the catalytic cracking process.

[0023] The main disadvantages of catalytic cracking technology:

[0024] 1) Oxygen co-feed makes the cracking reaction difficult to control, and it is easy to cause various side reactions such as excessive cracking, oxidative dehydrogenation, and deep oxidation;

[0025] 2). During the catalytic cracking reaction, CO X Excessive emissions;

[0026] 3) The reaction consumes a lot of energy, and the oxygen production process requires a high-energy air separation device (accounting for about 1 / 3 of the energy consumption of the entire dehydrogenation process);

[0027] 4). Mixing petroleum hydrocarbons and O2 as feed materials poses a huge safety hazard during the reaction process, making industrial application difficult. Summary of the invention

[0028] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a molecular sieve composite catalyst and a new method for preparing light olefins and aromatics by oxidative cracking of naphtha.

[0029] The present invention combines the Pechini sol-gel method and the impregnation method to prepare a series of alkali metal salt-modified ABO3 type perovskite composite oxygen carriers (L-Na2MoO4@CaMn 0.8 F 0.2 O3). The metal-modified molecular sieve T-ZSM-5 was prepared by ion exchange method to exchange the metal of ZSM-5 molecular sieve framework with the exogenous metal. Then the modified perovskite-molecular sieve composite catalyst (T-ZSM-5 (r) & L-Na2MoO4@CaMn X F 1-X O3). Different metals are used to dope the CaMnO3 perovskite oxygen carrier at the B position and the alkali metal salt Na2MoO4 feed amount is controlled to adjust the content and reaction activity of the perovskite oxygen carrier lattice oxygen. Different metals are used to ion exchange the ZSM-5 molecular sieve to adjust the strength and distribution of the acid center of the zeolite molecular sieve, so as to realize the design and regulation of the active center of the naphtha chemical chain oxidation cracking reaction.

[0030] The technical solution of the present invention is:

[0031] The present invention provides a molecular sieve composite catalyst, the catalyst composition is: T-ZSM-5 (r) & L-Na2MoO4@CaMn 0.8 F 0.2 O3, wherein metal T is any one of Ca, Mg, Y, Zr, Sr, r is any one of 50, 80, 130, 200, 260, metal F is any one of Cu, Fe, Co, Mo, and the loading amount L is any one of 0, 10%, 20%, 30%, 40%.

[0032] Preferably, the preparation method of the molecular sieve composite catalyst comprises: preparing CaMn doped with different metal F by a sol-gel method. 0.8 F 0.2 O3 perovskite oxygen carrier, and then L-Na2MoO4@CaMn with different loading amounts were prepared by impregnation method. 0.8 F 0.2 O3 composite perovskite oxygen carrier; different metal modified molecular sieves T-ZSM-5 were prepared by ion exchange method, and finally molecular sieve composite catalysts were prepared by mechanical mixing, T-ZSM-5(r) & L-Na2MoO4@CaMn 0.8 F0.2 O3.

[0033] Preferably, the different metal F-doped CaMn 0.8 F 0.2 The preparation method of O3 oxygen carrier comprises: according to the molecular formula of perovskite oxygen carrier to be prepared, CaMn 0.8 F 0.2 O3, F = Cu, Fe, Co, Mo, confirm the metal cation composition, and weigh the nitrate containing the corresponding cation and dissolve it in deionized water to form a nitrate solution, then add citric acid and ethylene glycol to the nitrate solution to form a mixed system, and finally heat and stir the mixed system at 80 ℃-90 ℃ to form a sol, and the sol is dried at 80 ℃-90 ℃, calcined at 400 ℃-500 ℃ for 1 h-3 h, calcined at 900 ℃-1000 ℃ for 7-9 h, cooled to room temperature and ground to obtain CaMn doped with different metals. 0.8 F 0.2 O3 oxygen carrier.

[0034] The room temperature is preferably 20°C-30°C.

[0035] Preferably, the different loading amounts of L-Na2MoO4@CaMn 0.8 F 0.2 The preparation method of O3 composite oxygen carrier comprises: weighing Na2MoO4 and dissolving it in deionized water, and then 0.8 Cu 0.2 O3 mass ratio is 0~2:5, and CaMn is added 0.8 F 0.2 O3 perovskite oxygen carrier, after being mixed evenly, transferred to 20 ℃-30 ℃ for ultrasonic treatment to form a mixed solution, the mixed solution was vacuum dried at 80 ℃-90 ℃, and calcined at 900 ℃-1000 ℃ for 4-6 h to obtain composite perovskite oxygen carriers L-Na2MoO4@CaMn with different alkali metal loadings. 0.8 F 0.2 O3, L = 0, 10%, 20%, 30%, 40%.

[0036] Preferably, the preparation method of the different metal modified molecular sieve T-ZSM-5 includes: adding metal nitrate to deionized water to prepare a 0.1-0.15 mol / L metal precursor solution, then adding ZSM-5 molecular sieves with different silicon-aluminum ratios r to form a mixed system, heating the mixed system at 80°C-90°C and stirring for 11-13 h, filtering the mixed system under reduced pressure and washing it with pure water for multiple times, repeating the metal ion exchange process again, and drying the obtained solid product at 100°C-110°C and calcining at 400°C-500°C for 4-6 h to obtain ZSM-5 molecular sieves T-ZSM-5(r) modified with different metals, wherein T = Ca, Mg, Y, Zr, Sr, r = 50, 80, 130, 200, 260.

[0037] Preferably, the preparation method of the molecular sieve composite catalyst includes: the preparation method of the molecular sieve composite catalyst includes: mechanically mixing the composite oxygen carrier and the metal-modified molecular sieve in a mass ratio of composite perovskite oxygen carrier to metal-modified molecular sieve (4-6):2 to obtain the molecular sieve composite catalyst.

[0038] The present invention also provides a novel method for preparing light olefins and aromatics by oxidative cracking of naphtha, wherein the naphtha raw material is contacted with a catalyst, and an oxidative cracking reaction of the catalyst is carried out under the conditions of 600-800°C, an air flow rate of 25-45 mL / min, a naphtha feed amount of 0.1-0.5 g, and a reaction time of 300-420 s per oxidation-reduction cycle, and the reaction flow is separated to obtain the target products of light olefins and aromatics. After the cracking reaction, the molecular sieve composite catalyst is oxidatively regenerated by an air flow of 80-95 mL / min; the catalyst is any one of the molecular sieve composite catalysts mentioned above;

[0039] Alternatively, the catalyst is composed of: CaMn 0.8 F 0.2 O3, wherein the metal F is any one of Cu, Fe, Co, Mo;

[0040] Alternatively, the catalyst is composed of: L-Na2MoO4@CaMn 0.8 F 0.2 O3, wherein the metal F is any one of Cu, Fe, Co, and Mo, and the loading amount L is any one of 0, 10%, 20%, 30%, and 40%.

[0041] Preferably, the reacted perovskite oxygen carrier is oxidized and regenerated in an air flow of 25-45 mL / min to replenish the consumed lattice oxygen.

[0042] The present invention will be further explained and described below:

[0043] The present invention is a novel naphtha chemical chaining oxidation cracking process developed based on chemical chaining combustion technology. By constructing a dual-function catalyst with oxygen-carrying and oxidation cracking capabilities, the process of producing light olefins by oxidation cracking of naphtha is realized in the absence of gaseous oxygen. This process includes oxidation cracking and oxygen carrier regeneration steps. In the oxidation cracking reaction, the alkane substrate is cracked on the metal active component to form light olefins. The lattice oxygen in the oxygen carrier oxidizes part of the generated hydrogen into water vapor in situ, which promotes the movement of the cracking reaction equilibrium in the positive direction and improves the conversion capacity of the substrate. After the reaction is completed, the oxygen carrier that has lost the lattice oxygen can be oxidized and regenerated in the air, and the carbon deposits are removed while the lattice oxygen is replenished to restore the reaction activity.

[0044] Compared with the traditional industrial naphtha catalytic oxidation cracking technology, the chemical chain oxidation cracking technology uses the effect of oxygen carrier lattice oxygen to decompose the cracking reaction into two gas-solid reactions (oxidation reaction and reduction reaction), which not only eliminates the resource- and energy-intensive air separation process, but also avoids direct contact between naphtha and air, eliminating potential safety hazards, allowing the reaction to be carried out under a higher petroleum hydrocarbon partial pressure, and further improving the reaction conversion rate. At the same time, the consumed lattice oxygen used by the oxygen carrier in the naphtha oxidation cracking reaction will release a large amount of heat to supply the cracking reaction during the oxidation and regeneration process in the air, realizing the self-heating operation of the cracking process, and greatly reducing the process energy consumption.

[0045] Bifunctional catalysts usually use transition metal oxides as active components and metal oxide materials with excellent oxygen storage and release capabilities as oxygen carriers to provide lattice oxygen for the reaction system. Compared with single metal oxidation, composite metal oxides are mostly non-stoichiometric. Among them, ABO3-type perovskite oxygen carriers are widely used in chemical chaining processes due to their good oxygen storage / release capacity, stable redox cycle performance and excellent mechanical lightness. By changing the type of metal elements at the A and B positions of the ABO3-type perovskite oxygen carrier and partially replacing the A or B position atoms in the lattice with other metal heteroatoms, different concentrations of lattice defects are generated and the lattice oxygen content is regulated to obtain perovskite oxygen carriers with different lattice oxygen contents and activities.

[0046] However, under high temperature reaction conditions, the lattice oxygen of the perovskite oxygen carrier tends to migrate from the bulk phase to the non-selective electrophilic oxygen species ( O - and O 2- etc.) evolution, leading to excessive oxidation of hydrocarbons to produce CO X(CO, CO2), thereby reducing the selectivity of the target product. Existing studies have shown that loading alkali metals or alkali metal salts on the surface of perovskite oxygen carriers can effectively inhibit the conversion of lattice oxygen species to non-selective electrophilic oxygen species. Although this strategy effectively improves the selection of target products, it also inhibits the conversion of substrates. Zeolite molecular sieves represented by ZSM-5 have suitable acidity, adjustable pore structure and good shape selectivity, and are widely used in low-temperature catalytic cracking (non-oxidative) reactions of naphtha. However, the coking produced during the naphtha cracking reaction can easily lead to the deactivation of zeolite molecular sieves, thereby reducing the reaction efficiency. Although it can be regenerated by air / oxygen and compensate for part of the reaction heat, the reaction process is still highly endothermic.

[0047] Based on this, a modified perovskite oxide and molecular sieve composite bifunctional catalyst was constructed. Among them, the rich and appropriately strong acidic centers of zeolite molecular sieve can effectively reduce the activation energy of CH breakage of petroleum hydrocarbons and thus reduce the cracking reaction temperature; while the lattice oxygen of ABO3 type perovskite oxygen carrier can promote the forward movement of the cracking reaction through selective hydrogen combustion (SHC) to improve the catalytic reaction activity; it can also inhibit the formation of zeolite molecular sieve coking through oxidation reaction to improve its coke resistance. By regulating the number and activity of lattice oxygen in the composite catalyst, designing the oxidative cracking active center, and introducing more acidic sites on the surface of zeolite molecular sieve, a highly efficient bifunctional catalyst with both naphtha alkane CH activation and oxidative cracking activity is designed and prepared, which is applied to naphtha chemical chain oxidative cracking reaction.

[0048] Compared with the prior art, the present invention has the following beneficial effects:

[0049] 1. The present invention provides a molecular sieve composite catalyst, the catalyst composition is: T-ZSM-5(r) & L-Na2MoO4@CaMn 0.8 F 0.2O3, firstly, an alkali metal salt-loaded ABO3 perovskite composite oxygen carrier was prepared to regulate the lattice oxygen content and reaction activity of the ABO3 perovskite composite oxygen carrier. Then a series of T-ZSM-5 molecular sieves modified with different metals were synthesized to regulate the strength and distribution of the acidic center of the ZSM-5 zeolite molecular sieve; the lattice oxygen release rate and the evolution to selective electrophilic oxygen species of the alkali metal-modified ABO3 perovskite composite oxygen carrier were modulated, making its lattice oxygen more active in oxidative cracking reactions, improving the yield of light olefins and aromatics, but this also reduced the substrate conversion capacity of the perovskite oxygen carrier. The rich and appropriately strong acidic centers of the metal-modified ZSM-5 zeolite molecular sieve reduce the CH cleavage activation energy of hydrocarbons in naphtha, thereby effectively reducing the temperature of the naphtha cracking reaction. In addition, the SHC reaction of the lattice oxygen of the perovskite composite oxygen carrier with the by-product hydrogen of the cracking reaction shifts the reaction equilibrium forward and promotes the conversion of the substrate. At the same time, the oxidation reaction of lattice oxygen effectively inhibits the coking and deactivation of ZSM-5 molecular sieve in traditional oxidative cracking reactions, greatly improving the coke resistance of the composite catalyst.

[0050] 2. From the data of Table 1, Table 2 and Table 3 of the embodiments of the present invention, it can be seen that the catalyst in Table 1 is catalytically reacted at a reaction temperature of 800 ° C, the catalyst in Table 2 is catalytically reacted at a reaction temperature of 750 ° C, and the catalyst in Table 3 is catalytically reacted at 650 ° C. As the composition of the catalyst changes, the catalytic reaction temperature decreases, proving that the catalytic performance is gradually enhanced. In addition, in comparison of catalysts with the same elemental composition, the selectivity of low-carbon olefins in Table 2 is increased compared with Table 1 (the selectivity is also increased under the premise of lowering the reaction temperature). The conversion rate and yield of Table 3 are significantly increased compared with Table 1 and Table 2 (under the premise of lowering the reaction temperature), proving that a synergistic effect is produced between the various parts of the catalyst of the present invention.

[0051] 3. The present invention discloses a novel method for producing low-carbon olefins and aromatics by oxidative cracking of naphtha. The catalyst of the present invention is applied to the reaction of producing low-carbon olefins by chemical chain oxidative cracking of naphtha, and the lattice oxygen of the perovskite composite oxygen carrier assisted by molecular sieve acts on the oxidative cracking reaction of naphtha. This not only eliminates the resource- and energy-intensive air separation process in the traditional oxidative cracking technology, but also avoids the CO induced by the co-feeding of oxygen in the traditional oxidative cracking technology. XIn addition, the lattice oxygen consumed in the oxygen carrier naphtha oxidation cracking reaction will release a large amount of heat to supply the cracking reaction during the oxidation regeneration process in the air, realizing the transformation of the naphtha oxidation cracking reaction from highly self-absorption of heat to self-heating, greatly reducing the process energy consumption. In the process of naphtha chemical chain oxidation cracking, the SHC reaction of the lattice oxygen of the perovskite composite oxygen carrier and the by-product hydrogen of the cracking reaction shifts the reaction equilibrium in the positive direction and promotes the conversion of the substrate. At the same time, the oxidation reaction effectively inhibits the formation of molecular sieve coking and improves the coke resistance of the composite catalyst.

[0052] The detailed structure of the present invention is further described below in conjunction with the accompanying drawings and specific implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 CaMn 0.8 F 0.2 O3 perovskite composite oxygen carrier (F = Cu, Fe, Co, Mo) application performance test data chart;

[0054] Figure 2 It is L-Na2MoO4@CaMn 0.8 Cu 0.2 O3 perovskite composite oxygen carrier (L = 0, 10%, 20%, 30%, 40%) application performance test data chart;

[0055] Figure 3 T-ZSM-5(r) & 30%-Na2MoO4@CaMn 0.8 Cu 0.2 One of the test data of the application performance test of O3 molecular sieve-assisted perovskite composite oxygen carrier (T = Ca, Mg, Y, Zr, Sr; r = 50, 80, 130, 200, 260). In the figure, MO represents 30%-Na2MoO4@CaMn 0.8 Cu 0.2 O3 composite perovskite oxide;

[0056] Figure 4 T-ZSM-5(r) & 30%-Na2MoO4@CaMn 0.8 Cu 0.2 Figure 2 of the application performance test data of O3 molecular sieve-assisted perovskite composite oxygen carrier (T = Ca, Mg, Y, Zr, Sr; r = 50, 80, 130, 200, 260). In the figure, MO represents 30%-Na2MoO4@CaMn 0.8 Cu 0.2 O3 composite perovskite oxide. DETAILED DESCRIPTION

[0057] Example 1 CaMn 0.8 F 0.2 Synthesis of O3 (F = Cu, Fe, Co, Mo)

[0058] (1) CaMn 0.8 Cu 0.2 Synthesis of O3:

[0059] Ca(NO3)2, Mn(NO3)2, and Cu(NO3)2 with a stoichiometric ratio of Ca: Mn: Cu = 5: 4: 1 were dissolved in 40 mL of deionized water and stirred at 40 °C for 0.5 h. After the metal salts were fully dissolved, citric acid was used as a complexing agent and the mixture was added with a cation (Ca 2+ , Mn 2+ , Cu 2+ ) citric acid with a molar ratio of 2.5: 1, stirred at 500 rpm and 40 ° C for 0.5 h. Then, ethylene glycol (99.8%) with a molar ratio of 1.5: 1 to citric acid was added, and then the temperature was raised to 80 ° C and stirred until the mixture formed a sol. The obtained solid product was placed in an 80 ° C vacuum drying oven and dried overnight, and placed in a muffle furnace and programmed to 450 ° C for calcination for 1 h, and then raised to 950 ° C for calcination for 8 h (heating rate of 10 ° C / min), cooled to room temperature and ground into a powdered solid less than 10 mesh to obtain CaMn 0.8 Cu 0.2 O3 perovskite composite oxygen carrier.

[0060] (2) CaMn 0.8 Co 0.2 Synthesis of O3:

[0061] Ca(NO3)2, Mn(NO3)2, and Co(NO3)2∙6H2O with a stoichiometric ratio of Ca: Mn: Co = 5: 4: 1 were dissolved in 40 mL of deionized water and stirred at 40 °C for 0.5 h. After the metal salts were fully dissolved, citric acid was used as a complexing agent and the mixture was added with metal cations (Ca 2+ , Mn 2+ 、Co 2+) citric acid with a molar ratio of 2.5: 1, stirred at 500 rpm and 40 ° C for 0.5 h. Then, ethylene glycol (99.8%) with a molar ratio of 2.5: 1 to citric acid was added, and then the temperature was raised to 85 ° C and stirred until the mixture formed a sol. The obtained solid product was placed in a 90 ° C vacuum drying oven for drying overnight, and placed in a muffle furnace and programmed to 500 ° C for calcination for 1.5 h, and then raised to 950 ° C for calcination for 7 h (heating rate of 10 ° C / min), cooled to room temperature and ground into a powdered solid less than 10 mesh to obtain CaMn 0.8 Co 0.2 O3 perovskite composite oxygen carrier.

[0062] (3) CaMn 0.8 Fe 0.2 Synthesis of O3:

[0063] Ca(NO3)2, Mn(NO3)2, Fe(NO3)3∙9H2O with a stoichiometric ratio of Ca: Mn: Fe = 5: 4: 1 were dissolved in 40 mL of deionized water and stirred at 40 °C for 0.5 h. After the metal salts were fully dissolved, citric acid was used as a complexing agent and the mixture was added with metal cations (Ca 2+ , Mn 2+ , Fe 3+ ) citric acid with a molar ratio of 2: 1, stirred at 500 rpm and 40 °C for 0.5 h. Then, ethylene glycol (99.8%) with a molar ratio of 1.5: 1 to citric acid was added, and then the temperature was raised to 80 °C and stirred until the mixture formed a sol. The obtained solid product was placed in an 85 °C vacuum drying oven and dried overnight, and placed in a muffle furnace and programmed to 480 °C for calcination for 2 h, and then raised to 1000 °C for calcination for 8 h (heating rate of 10 °C / min), cooled to room temperature and ground into a 1-10 mesh powder solid to obtain CaMn 0.8 Fe 0.2 O3 perovskite composite oxygen carrier.

[0064] (4) CaMn 0.8 Mo 0.2 Synthesis of O3:

[0065] Ca(NO3)2, Mn(NO3)2, and Mo(NO3)3∙5H2O with a stoichiometric ratio of Ca: Mn: Mo = 5: 4: 1 were dissolved in 40 mL of deionized water and stirred at 40 °C for 0.5 h. After the metal salts were fully dissolved, citric acid was used as a complexing agent and the mixture was added with metal cations (Ca 2+ , Mn 2+ 、Mo 3+) citric acid with a molar ratio of 2.5: 1, stirred at 500 rpm and 40°C for 0.5 h. Then, ethylene glycol (99.8%) with a molar ratio of 2:1 to citric acid was added, and then the temperature was raised to 90°C and stirred until the mixture formed a sol. The obtained solid product was placed in a 90°C vacuum drying oven and dried overnight, and placed in a muffle furnace and programmed to rise to 450°C for calcination for 3 h, and then raised to 900°C for calcination for 9 h (heating rate of 10°C / min), cooled to room temperature and ground into a powdered solid less than 10 mesh to obtain CaMn 0.8 Mo 0.2 O3 perovskite composite oxygen carrier.

[0066] The CaMn prepared in Example 1 0.8 F 0.2 The O3 (F = Cu, Fe, Co, Mo) catalyst was pressed into tablets, passed through a 20-40 mesh sieve, and loaded into a fixed bed reactor. Naphtha and nitrogen were introduced into the reactor. Under certain reaction conditions, the catalytic oxidation cracking reaction was carried out, and the reactant flow was separated to obtain the target product, low-carbon olefins. The specific catalytic reaction performance data are shown in Table 1. The perovskite oxygen carrier after the reaction was oxidized and regenerated in an air flow of 25 mL / min to replenish the consumed lattice oxygen.

[0067] The specific reaction conditions in this example are: 0.5 g of catalyst, reaction temperature of 800° C., space velocity of 25 mL / min, naphtha feed amount of 0.5 g, and reaction time of each redox cycle of 420 s.

[0068]

[0069] Comparison of CaMn doped with different metal cations at B site in Table 1 0.8 M 0.2 The test data of the application performance of O3 perovskite oxide found that the change of different metal doped cations caused the crystal structure of ABO3 perovskite oxygen carrier (CaMnO3) to be distorted, which increased the surface lattice oxygen reaction activity and lattice oxygen migration rate of the oxygen carrier, thereby improving its catalytic cracking reaction performance.

[0070] Calculation method of conversion and selectivity in the examples: FU Li97Plus and Techcomp 7900 gas chromatographs were used to analyze the gas product components (low-carbon olefins, alkanes, aromatics, CO X , carbon deposition) and content, and their content is determined by external standard method. Naphtha conversion rate and product selectivity are calculated based on mass, and the specific formula is as follows:

[0071]

[0072] The target products are light olefins and aromatics, and our goal is high conversion rate and high selectivity of light olefins and aromatics.

[0073] Example 2 L-Na2MoO4@CaMn 0.8 F 0.2 Synthesis of O3 (L = 0, 10%, 20%, 30%, 40%; F = Cu, Fe, Co, Mo)

[0074] (1) 30%-Na2MoO4@CaMn 0.8 Cu 0.2 Synthesis of O3:

[0075] Ca(NO3)2, Mn(NO3)2, and Cu(NO3)2 with a stoichiometric ratio of Ca: Mn: Cu = 5: 4: 1 were dissolved in 40 mL of deionized water and stirred at 40 °C for 0.5 h. After the metal salts were fully dissolved, citric acid was used as a complexing agent and the mixture was added with a metal cation (Ca 2+ , Mn 2+ , Cu 2+ ) citric acid with a molar ratio of 2.5: 1, stirred at 500 rpm and 40 °C for 0.5 h. Then, ethylene glycol (99.8%) with a molar ratio of 1.5: 1 to citric acid was added, and then the temperature was raised to 80 °C and stirred until the mixture formed a sol. The obtained solid product was placed in an 80 °C vacuum drying oven and dried overnight, and placed in a muffle furnace and programmed to rise to 450 °C for calcination for 1 h, and then raised to 950 °C for calcination for 8 h (heating rate of 10 °C / min) to obtain a composite perovskite oxide CaMn 0.8 Cu 0.2 O3.

[0076] Add 0.3 g Na2MoO4 and 10 mL deionized water accurately weighed into a 25 mL beaker and dissolve in it. Stir and dissolve at room temperature. After dissolution is complete, add 1 g of the CaMn prepared above. 0.8 Cu 0.2 O3 perovskite composite oxygen carrier. Among them, Na2MoO4 and CaMn 0.8 Cu 0.2The mass ratio of O3 is 0.3. After stirring until uniformly dispersed, the mixture is transferred to a 25 ℃ ultrasonic cleaner for ultrasonic treatment for 1 h. Then, the beaker is placed in a water bath and stirred at 250 rpm for 2 h. After stirring, it is allowed to stand for 2 h, and the mixture is transferred to an 80 ℃ vacuum drying oven and dried overnight. After drying, the obtained solid product is placed in a 900 ℃ muffle furnace for calcination for 5 h (heating rate of 10 ℃ / min), cooled to room temperature and ground into a powdered solid less than 10 mesh to obtain 30%-Na2MoO4@CaMn 0.8 Cu 0.2 O3.

[0077] According to the method of Example 2, L-Na2MoO4@CaMn 0.8 Cu 0.2 O3 (L = 0, 10%, 20%, 30%, 40%; F = Cu, Fe, Co, Mo) catalyst was pressed into tablets, passed through a 20-40 mesh sieve, and loaded into a fixed bed reactor. Naphtha and nitrogen were introduced into the reactor. Under certain reaction conditions, catalytic oxidation cracking reaction was carried out, and the reactant flow was separated to obtain the target product, low-carbon olefins. The specific catalytic reaction performance data are shown in Table 2. The perovskite oxygen carrier after the reaction was oxidized and regenerated in an air flow of 30 mL / min to replenish the consumed lattice oxygen.

[0078] The specific reaction conditions of this example are: 0.5 g of catalyst, reaction temperature of 750° C., space velocity of 25 mL / min, naphtha feed amount of 0.5 g, and reaction time of each redox cycle of 420 s.

[0079]

[0080] Comparison of L-Na2MoO4@CaMn with different Na2MoO4 alkali metal salt loadings in Table 2 0.8 F 0.2 The test data of the application performance of O3 perovskite composite oxygen carriers found that after modification with alkali metals, the conversion rate of perovskite oxygen carrier substrates showed a downward trend and was negatively correlated with the loading amount, while the selectivity of the target product was positively correlated. Na2MoO4 alkali metal salt CaMn 0.8 Cu 0.2 O3 perovskite forms a core-shell structure, which can inhibit the transformation of lattice oxygen species in the oxygen carrier into non-selective electrophilic oxides, accompanied by the phase transition of the oxygen carrier and O2 2- The alkali metal salt modulates the migration rate of oxygen, inhibits the over-oxidation of light olefins, and thus significantly increases the olefin yield.

[0081] Example 3 T-ZSM-5 (r) & 30%-Na2MoO4@CaMn 0.8 Cu 0.2 Synthesis of O3 (T = Ca, Mg, Y, Zr, Sr; r = 50, 80, 130, 200, 260)

[0082] (1)Sr-ZSM-5 (80) & 30%-Na2MoO4@CaMn 0.8 Cu 0.2 Synthesis of O3:

[0083] 2.0 g ZSM-5 (80) molecular sieve and 20 mL 0.1 mol / L strontium nitrate solution were added to a 50 mL round-bottom flask and metal exchanged in an 80 ℃ oil bath for 12 h. The mixed solution was filtered under reduced pressure and washed with pure water several times, and the metal ion exchange process was repeated again. The obtained solid product was placed in a 100 ℃ oven to dry overnight. After drying, it was placed in a muffle furnace and calcined at 450 for 6 h (heating rate of 5 ℃ / min). After cooling to room temperature, the solid product was ground into a powdery solid less than 10 mesh to obtain Sr-ZSM-5 (80).

[0084] The perovskite composite oxygen carrier (30%-Na2MoO4@CaMn 0.8 Cu 0.2 O3) and molecular sieve (Sr-ZSM-5 (80)), and the two were mixed evenly by physical and mechanical mixing to obtain a molecular sieve-assisted perovskite composite oxygen carrier catalytic system (Sr-ZSM-5 (80) & 30%-Na2MoO4@CaMn 0.8 Cu 0.2 O3).

[0085] T-ZSM-5 (80) & 30%-Na2MoO4@CaMn were prepared according to the method of Example 3. 0.8 Cu 0.2 O3 (T =Ca, Mg, Y, Zr, Sr) catalyst, which was pressed into tablets, passed through a 20-40 mesh sieve, and loaded into a fixed bed reactor, and naphtha and nitrogen were introduced into the reactor. Under certain reaction conditions, a catalytic oxidation cracking reaction was carried out, and the reactant stream was separated to obtain the target product, light olefins. The specific catalytic reaction performance data are shown in Table 3. The perovskite oxygen carrier after the reaction was oxidized and regenerated in an air flow of 45 mL / min to replenish the consumed lattice oxygen.

[0086] (2)Ca-ZSM-5 (200) & 30%-Na2MoO4@CaMn 0.8 Cu0.2 Synthesis of O3:

[0087] 2.0 g ZSM-5 (200) molecular sieve and 20 mL 0.1 mol / L calcium nitrate solution were added to a 50 mL round-bottom flask and metal exchanged in an 80 ℃ oil bath for 12 h. The mixed solution was filtered under reduced pressure and washed with pure water several times, and the metal ion exchange process was repeated again. The obtained solid product was placed in a 100 ℃ oven to dry overnight. After drying, it was placed in a muffle furnace and calcined at 450 for 6 h (heating rate of 5 ℃ / min). After cooling to room temperature, the solid product was ground into a powdery solid less than 10 mesh to obtain Ca-ZSM-5 (200).

[0088] The perovskite composite oxygen carrier (30%-Na2MoO4@CaMn 0.8 Cu 0.2 O3) and molecular sieve (Ca-ZSM-5 (200)), and the two were mixed evenly by physical and mechanical mixing to obtain a molecular sieve-assisted perovskite composite oxygen carrier catalytic system (Ca-ZSM-5 (200)&30%-Na2MoO4@CaMn 0.8 Cu 0.2 O3).

[0089] The Ca-ZSM-5 (200)&30%-Na2MoO4@CaMn prepared in Example 3 0.8 Cu 0.2 O3 (r= 50, 80,130, 200, 260) catalyst tablets were passed through a 20-40 mesh sieve and loaded into a fixed bed reactor. Naphtha and nitrogen were introduced into the reactor. Catalytic oxidation cracking reaction was carried out under certain reaction conditions, and the reactant flow was separated to obtain the target product, low-carbon olefins. The specific catalytic reaction performance data are shown in Table 3. The perovskite oxygen carrier after the reaction was oxidized and regenerated in an air flow of 25-45 mL / min to replenish the consumed lattice oxygen.

[0090] Other metal ion exchange (Ca, Mg, Y, Zr) with different Si / Al ratios (50, 80, 130, 200, 260) molecular sieve-assisted perovskite composite oxygen carrier T-ZSM-5 (r) & 30%-Na2MoO4@CaMn 0.8 Cu 0.2The preparation method of O3 (T = Ca, Mg, Y, Zr; r = 50, 80, 130, 200, 260) is the same as the above-mentioned embodiment. The mass ratio of the physical and mechanical mixing of the molecular sieve and the perovskite composite metal oxide is 5: 2. The prepared molecular sieve-assisted perovskite composite oxygen carrier catalyst is pressed into tablets, passed through a 20-40 mesh sieve, loaded into a fixed bed reactor, and naphtha and nitrogen are introduced into the reactor. Under certain reaction conditions, a catalytic oxidation cracking reaction is carried out, and the reactant flow is separated to obtain the target product, low-carbon olefins. The specific catalytic reaction performance data are shown in Table 3. The perovskite oxygen carrier after the reaction is oxidized and regenerated in an air flow of 25-45 mL / min to replenish the consumed lattice oxygen.

[0091] The reaction conditions of Example 3 were as follows: 0.5 g of catalyst, 650° C. reaction temperature, 25 mL / min space velocity, 0.5 g of naphtha feed, and 420 s reaction time for each redox cycle.

[0092]

[0093] Comparison of different T-ZSM-5(r) & 30%-Na2MoO4@CaMn in Table 3 0.8 Cu 0.2 The test data of the application performance of O3 molecular sieve-perovskite composite oxygen carrier found that the introduction of molecular sieves in the catalytic reaction system reduces the CH bond activation energy of petroleum hydrocarbons, reduces the reaction temperature and greatly improves the substrate conversion capacity. At the same time, the active metal is introduced into the ZSM-5 molecular sieve framework through ion exchange, which regulates the strength and distribution of the acid center of the zeolite molecular sieve and further improves the selectivity of light olefins.

[0094] Literature shows that the important parameters of zeolite molecular sieves in industrial applications, such as activity, selectivity, and stability, are closely related to the Si / Al ratio and aluminum distribution of the zeolite. The Si / Al ratio significantly affects the acidic properties of zeolite molecular sieves: as the Si / Al ratio increases, the Bronsted acid sites of the molecular sieve decrease, while the Lewis acid sites increase. Compare Sr-ZSM-5(r) & 30%-Na2MoO4@CaMn in Table 3 0.8 Cu 0.2 The test data of the application performance of O (r = 50, 80, 130, 200, 260) molecular sieve-perovskite composite oxygen carrier showed that the silicon-aluminum ratio of Sr-ZSM-5 molecular sieve was negatively correlated with the conversion rate of petroleum hydrocarbon substrates, and positively correlated with low-carbon olefins. The suitable Lewis acid sites of zeolite molecular sieves are conducive to the cleavage of CH bonds of petroleum hydrocarbons, promoting the conversion of substrates and the selectivity of target products.

[0095] Based on the chemical chain technology, a new process for naphtha oxidation cracking was developed, which achieved efficient conversion of naphtha to low-carbon olefins in the absence of gaseous oxygen. This technology eliminates the energy and resource-intensive air separation process in the traditional naphtha cracking process. The selective hydrogen combustion reaction of the oxygen carrier lattice oxygen breaks the equilibrium of the cracking reaction and moves it forward, thereby improving the conversion of hydrocarbons in naphtha. At the same time, a large amount of heat released during the oxidation regeneration of the oxygen carrier is directly supplied to the reaction, realizing the transformation of the cracking reaction from highly self-absorption of heat to self-heating, which greatly reduces energy consumption. In addition, direct contact between naphtha hydrocarbons and gaseous oxygen is avoided, eliminating potential safety hazards.

[0096] A series of modified perovskite composite oxygen carriers were prepared by combining the sol-gel method and the impregnation method, and a series of metal-modified ZSM-5 molecular sieves were designed and constructed by the metal ion exchange method. After screening and selection, a highly efficient bifunctional catalyst with both naphtha alkane CH activation and oxidative cracking activity was constructed by mechanical and physical mixing methods, realizing the efficient preparation of light olefins by oxidative cracking of naphtha at low temperature. In addition, lattice oxygen can inhibit the formation of coking of zeolite molecular sieves through oxidation reactions, effectively solving the disadvantage of easy carbon deposition and deactivation of molecular sieve catalysts in traditional industries.

[0097] In summary, the novel technology of naphtha oxidation cracking to produce light olefins based on chemical chain technology in the present invention realizes the efficient conversion of naphtha to light olefins. It effectively reduces the reaction energy consumption and CO X It reduces emissions and effectively avoids the problem of traditional molecular sieve catalysts being prone to carbon deposition and deactivation.

[0098] The above is a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, can make equivalent replacements or changes according to the technical solutions and concepts of the present invention, which should be covered by the protection scope of the claims of the present invention.

Claims

1. A molecular sieve composite catalyst, characterized in that: The composition of the catalyst is: T-ZSM-5 & L-Na2MoO4@CaMn 0.8 F 0.2 O3, wherein the metal T is any one of Ca, Mg, Y, Zr, Sr, the silicon-aluminum ratio of ZSM-5 is any one of 50, 80, 130, 200, the metal F is Cu, and the loading amount L is any one of 10%, 20%, 30%, 40%; the molecular sieve composite catalyst is a catalyst for oxidative cracking of naphtha to produce light olefins and aromatics, L-Na2MoO4@CaMn 0.8 F 0.2 Mass ratio of O3 to T-ZSM-5 (4-6):

2.

2. The molecular sieve composite catalyst according to claim 1, characterized in that: The preparation method of the molecular sieve composite catalyst comprises: preparing CaMn doped with different metal F by sol-gel method; 0.8 F 0.2 O3 perovskite oxygen carrier, and then L-Na2MoO4@CaMn with different loading amounts were prepared by impregnation method. 0.8 F 0.2 O3 composite perovskite oxygen carrier; different metal modified molecular sieves T-ZSM-5 were prepared by ion exchange method, and finally molecular sieve composite catalysts were prepared by mechanical physical mixing, T-ZSM-5 & L-Na2MoO4@CaMn 0.8 F 0.2 O3.

3. The molecular sieve composite catalyst according to claim 2, characterized in that: The different metal F-doped CaMn 0.8 F 0.2 The preparation method of O3 oxygen carrier comprises: according to the molecular formula of perovskite oxygen carrier to be prepared, CaMn 0.8 F 0.2 O3, F = Cu, confirm the metal cation composition, and weigh the nitrate containing the corresponding cation and dissolve it in deionized water to form a nitrate solution, then add citric acid and ethylene glycol to the nitrate solution to form a mixed system, and finally heat and stir the mixed system at 80 ℃ -90 ℃ to form a sol, the sol is dried at 80 ℃ -90 ℃, calcined at 400 ℃ -500 ℃ for 1 h -3h, calcined at 900 ℃ -1000 ℃ for 7-9 h, cooled to room temperature and ground to obtain perovskite oxygen carriers doped with different metals.

4. The molecular sieve composite catalyst according to claim 3, characterized in that The molar ratio of citric acid to metal cation is 2-2.5:1, and ethylene glycol is added in a molar ratio of 1.5-2.5:1 to citric acid.

5. The molecular sieve composite catalyst according to claim 2, characterized in that: The different loading amounts of L-Na2MoO4@CaMn 0.8 F 0.2 The preparation method of O3 composite oxygen carrier comprises: weighing Na2MoO4 and dissolving it in deionized water, and then 0.8 Cu 0.2 O3 mass ratio is 0~2:5, and CaMn is added 0.8 F 0.2 O3 perovskite oxygen carrier, after being mixed evenly, transferred to 20 ℃-30 ℃ for ultrasonic treatment to form a mixed solution, the mixed solution was vacuum dried at 80 ℃-90 ℃ and calcined at 900 ℃-1000 ℃ for 4-6 h to obtain composite perovskite oxygen carriers L-Na2MoO4@CaMn with different alkali metal loadings 0.8 F 0.2 O3, L = 10%, 20%, 30%, 40%.

6. The molecular sieve composite catalyst according to claim 2, characterized in that: The preparation method of the different metal modified molecular sieve T-ZSM-5 comprises: adding metal nitrate into deionized water to prepare 0.1-0.15 mol / L metal precursor solution, then adding ZSM-5 molecular sieves with different silicon-aluminum ratios to form a mixed system, heating the mixed system at 80°C-90°C and stirring for 11-13 hours, filtering the mixed system under reduced pressure and washing it with pure water for multiple times, repeating the metal ion exchange process again, and drying the obtained solid product at 100°C-110°C and calcining at 400°C-500°C for 4-6 hours to obtain the different metal modified ZSM-5 molecular sieve T-ZSM-5, wherein T = Ca, Mg, Y, Zr, Sr, and the silicon-aluminum ratio of ZSM-5 = 50, 80, 130, 200.

7. The molecular sieve composite catalyst according to claim 2, characterized in that: The preparation method of the molecular sieve composite catalyst comprises: mechanically mixing a composite perovskite oxygen carrier and a metal-modified molecular sieve in a mass ratio of (4-6):2 to obtain the molecular sieve composite catalyst.

8. A method for preparing light olefins and aromatics by oxidative cracking of naphtha, characterized in that: The naphtha raw material is contacted with the catalyst, and an oxidation cracking reaction of the catalyst is carried out under the conditions of 600-800°C, an air flow rate of 25-45 mL / min, a naphtha feed amount of 0.1-0.5 g, and a reaction time of 300-420 s per oxidation-reduction cycle, and the reaction flow is separated to obtain target products of light olefins and aromatics. After the cracking reaction, the molecular sieve composite catalyst is oxidized and regenerated by an air flow of 80-95 mL / min; The catalyst is any one of the molecular sieve composite catalysts in claims 1-7.

9. The method for preparing light olefins and aromatics by oxidative cracking of naphtha according to claim 8, characterized in that: The reacted perovskite oxygen carrier is oxidized and regenerated in an air flow of 25-45 mL / min to replenish the consumed lattice oxygen.